Trauma og minne i Jon Fosses Stengd gitar - Domsa, Zsófia (Scandinavistica Vilnensis, 2023)
Jon Fosse’s writing is characterized by a constant return to turmoil that is often associated with traumatic events in the past. His literary figures seem to be trapped in their painful memories. The very cause or starting point of their trauma often remains hidden or unsaid. The novel Closed Guitar from 1985 is about Liv, a young single mother who locks herself out of her apartment where her one-year-old son is. In the novel, we follow the thoughts of a lonely person who is closed as much inside as outside. The main character in the novel undergoes a mental journey into the past and is tossed back and forth between her autobiographical memories and hallucinations. Since the novel was published in 1985, memory research has undergone a revolution and researchers have pointed out that our memories and visions of the future are closely linked. In Fosse’s novel, bad and good memories are piled on top of one another, and thoughts about the future create an intense encounter between the outer and the inner reality.I discuss at how Liv’s dissociative tendency and her movements in the autobiographical memories form a self-narrative that, despite its fragmented character, creates a relevant context for her. The reader, on the other hand, struggles to interpret her narrative, because it is apparently shaped by false memories and several different variations of the same event. Liv’s story as fiction brings us closer to understanding how our autobiographical narratives are structured.
Keywords: Jon Fosse; dissociation; trauma theory; traumatic memory; memory research; cognitive literary theory